Queer Diagnoses: Parallels and Contrasts in the History of Homosexuality, Gender Variance, and the Diagnostic and Statistical Manual - Drescher, Jack (Archives of Sexual Behavior : The Official Publication of the International Academy of Sex Research, 2010)
The American Psychiatric Association (APA) is in the process of revising its Diagnostic and Statistical Manual (DSM), with the DSM-V having an anticipated publication date of 2012. As part of that ongoing process, in May 2008, APA announced its appointment of the Work Group on Sexual and Gender Identity Disorders (WGSGID). The announcement generated a flurry of concerned and anxious responses in the lesbian, gay, bisexual, and transgender (LGBT) community, mostly focused on the status of the diagnostic categories of Gender Identity Disorder (GID) (for both children and adolescents and adults). Activists argued, as in the case of homosexuality in the 1970s, that it is wrong to label expressions of gender variance as symptoms of a mental disorder and that perpetuating DSM-IV-TR’s GID diagnoses in the DSM-V would further stigmatize and cause harm to transgender individuals. Other advocates in the trans community expressed concern that deleting GID would lead to denying medical and surgical care for transgender adults. This review explores how criticisms of the existing GID diagnoses parallel and contrast with earlier historical events that led APA to remove homosexuality from the DSM in 1973. It begins with a brief introduction to binary formulations that lead not only to linkages of sexual orientation and gender identity, but also to scientific and clinical etiological theories that implicitly moralize about matters of sexuality and gender. Next is a review of the history of how homosexuality came to be removed from the DSM-II in 1973 and how, not long thereafter, the GID diagnoses found their way into DSM-III in 1980. Similarities and differences in the relationships of homosexuality and gender identity to psychiatric and medical thinking are elucidated. Following a discussion of these issues, the author recommends changes in the DSM-V and some internal and public actions that the American Psychiatric Association should take.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; discipline; inégalités; premier cycle; psychiatrie; régions géographiques; santé; sciences; sciences humaines; sexologie; soc2014; système médical; systèmes d'oppressions; thématiques; transidentité; violences; états-unis

Brain storm: The flaws in the science of sex differences - Jordan-Young, Rebecca M. (Harvard University Press, 2010)
Jordan-Young has written a stunning book that demolishes most of the science associated with the dominant paradigm of the development of sex and gender identity, behavior, and orientation. The current paradigm, brain organization theory, proposes: "Because of early exposure to different sex hormones, males and females have different brains"; and these hormones also create "gay" and "straight" brains. Jordan-Young interviewed virtually every major researcher in the field and reviewed hundreds of published scientific papers. Her conclusion: "Brain organization theory is little more than an elaboration of longstanding folk tales about antagonistic male and female essences and how they connect to antagonistic male and female natures." She explains, in exquisite detail, the flaws in the underlying science, from experimental designs that make no statistical sense to "conceptually sloppy" definitions of male and female sexuality, contradictory results, and the social construction of normality. Her conclusion that the patterns we see are far more complicated than previously believed and due to a wider range of variables will shake up the research community and alter public perception.
Keywords: LGBTQIA2+; analyse critique; approches et analyses; corps; cours; différence des sexes; discipline; discours dominant; identité sexuelle; identités LGBTQIA2+; neurosciences; premier cycle; psy4910; psychologie; revue de la littérature; sciences; sciences humaines; sexe/genre; sexisme; sociologie; systèmes d'oppressions; thématiques